TINJAUAN PENGIMPLEMENTASIAN ELECTRONIC HEALTH RECORD (EHR) PADA INSTALASI REKAM MEDIS DI RS AKADEMIK UNIVERSITAS GADJAH MADA YOGYAKARTA - , FUTIHATUR RAHMAWATI, Nuryati, M.PH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The Electronic Health Record is the latest technology that can facilitate the performance of personnel medical recorders and other health personnel. Yet many who have to implement the latest technology in the medical record installation in Indonesia. One that has been implemented EHR are UGM Academic Hospital. Objective: To determine the implementation of EHR systems, as well as identify existing constraints on the EHR in Medical Record Installation UGM Academic Hospital. Methods: The study was a descriptive study with a qualitative approach to data collection in phenomenology. Techniques of data collection by interview, observation, and documentation. Subjects in this study were medical records officer installation and IT officer, while the object of this study is the EHR system at UGM Academic Hospital. Results: Implementation Review of the medical records held at the outpatient registration, emergency care and hospitalization with entry social data, sub visit, sub service, then sub internal reference and synchronized directly to the computer doctor with the advent of notification. Encoding has also been implemented well and is easy to entry EHR diagnosis and the desired code appears. In addition to the newly implemented reporting RL 1.1 and RL 4.b for external, internal, while the hospital daily reports, visit reports, statements diagnosis list, reports of nursing actions and patient every doctor report. Problems were encountered in the implementation of the EHR is not the policy of the encoding delay, lack of data retrieval system development related to the implementation of reporting and the lack of manual books in the implementation of EHR systems.